2021
DOI: 10.1590/1982-4327e3134
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Syndrome and Consumption of Alcohol and Illicit Substances in University Students

Abstract: The consumption of alcohol and illicit substances has shown alarming levels among young university students, and its use may be associated with the coping strategy of academic burnout. This review aimed to synthesize the scientific evidence related to the consumption of alcohol and illicit substances associated with burnout syndrome in university students. Searches were carried out in: Biblioteca Virtual em Saúde, PubMed, Web of Science, PsycNet and Scopus databases, with no year limitation and based on the PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
4
0
2
Order By: Relevance
“…In the present research, we found that only one of the three components of burnout syndrome, depersonalization, positively predicts alcohol consumption, and that emotional exhaustion and achievement dissatisfaction do not, coinciding in part with previous findings that the relation between burnout syndrome and alcohol consumption can be partially attributed to other variables [44][45][46][47][48]50].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present research, we found that only one of the three components of burnout syndrome, depersonalization, positively predicts alcohol consumption, and that emotional exhaustion and achievement dissatisfaction do not, coinciding in part with previous findings that the relation between burnout syndrome and alcohol consumption can be partially attributed to other variables [44][45][46][47][48]50].…”
Section: Discussionsupporting
confidence: 90%
“…The relationship between burnout and alcohol consumption has been explored with mixed results [44][45][46]; some studies did not find a significant association between burnout and alcohol consumption or found an association only when another variable was present [47][48][49][50]. According to Frone [51], only those workers who cannot cope with stressors or have certain vulnerabilities use alcohol as a way of dealing with stress.…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…Contradictory findings on the use of tranquillisers have been reported in various studies (Erschens et al, 2018; Andrade et al, 2021). It is possible that students who were already taking tranquillisers at the beginning of this study were experiencing burnout or dealing with underlying mental health issues that put them at greater risk of burnout.…”
Section: Discussionmentioning
confidence: 77%
“…The vulnerable situations of the students, emotional conflicts in the academia environment, excess of activities and competitiveness are pointed as the most contributing factors in the development of high levels of stress and alcohol misuse. This excessive alcohol consumption may be viewed as a dysfunctional coping mechanism, since the students may abuse alcohol as a strategy for regulating tension and stressful situations in the academia [43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%